Advocacy 20 years on from Hampel: is it time we revisited the postgraduate teaching of advocacy?. Issue 4 (2nd October 2017) - Davies, Gemma Louise; Welsh, James
ABSTRACT: This paper seeks to discuss the teaching of advocacy as a discipline with specific reference to the way in which advocacy is taught on the Bar Professional Training Course in England and Wales. The Advocacy Training Council favours the Hampel Method of teaching advocacy first developed more than 20 years ago in Australia. The paper seeks to review the use of the Hampel Method by offering a critique of behaviourist learning theory from a constructivist standpoint and putting forward alternative teaching techniques which are in harmony with the principles of constructivism, experiential learning and productive failure. We conclude that the teaching of advocacy can be improved and that greater scholarship is needed in this important area to ensure students are taught using the best techniques.